PRIVACY, COVID-19 AND ONLINE TEACHING: A COMPARATIVE STUDY IN ESTONIA, FRANCE AND ISRAEL - Epstein, Dmitry; John, Nicholas; Wilhelm, Carsten; Barats, Christine; Siibak, Andra (AoIR Selected Papers of Internet Research, 2021)
The COVID-19 crisis is a potential watershed moment for privacy with profound long-term effects on the organization and practices of work, education, and civic engagement. In this study we focus on the profound re-negotiation of mediated personal boundaries in times of mass lockdowns and social distancing. To understand how these new social conditions might be playing out in the field of privacy, we interviewed 90 faculty in higher education in Estonia, France and Israel. Participants were asked about changes in their ICT use for personal and work purposes, with the practice of distance teaching serving as a common experience for the discussion of possible changes in their views and practices of privacy. Our findings point to the precedence of 2 considerations of privacy over 2 considerations. In other words, interviewees had very little to say about the broader forms of data collection by their employers, the state, or commercial companies that are enabled by the adoption of new ICTs. They did, though, have much to say about their mediated relations with students and colleagues, and were very much concerned with self-presentation and impression management as well as with sustaining meaningful teaching situations. In general, the prism of privacy unearths the hidden social structures of teaching and interacting online.